Network analysis of the food-energy-water nexus in the Gulf of Mexico (America) region - Casey L. Steadman; Shaun Williams; Andrew Eiswerth (Scientific Reports)
Abstract Increasing stress on and dependencies among the food, energy, and water sectors make historic approaches to managing resources from a single-sector perspective unsustainable. Although significant advances have been made in understanding food-energy-water (FEW) nexus dynamics, particularly at the global scale, approaches to regional analysis are needed that provide contextual detail, identify key actors, and help inform selection of the most appropriate strategies for building resilience. Moreover, because negative feedback loops among FEW sectors occur at multiple geographic scales (local, regional, national, global), conveying a holistic picture of FEW nexus concerns and opportunities is challenging. We propose an approach to scan grey literature (e.g., news media) and distill this information into useful insights on regionally important FEW nexus feedback loops and quantitative data for constructing geospatially anchored social networks. Furthermore, we showcase how integrating and embedding this qualitative and quantitative data into an ArcGIS StoryMap allows for interactive and layered communication of FEW tension points, regional hotspots, and key players, facilitating the ability for stakeholders to obtain and build a multi-scale, holistic perspective of FEW nexus dynamics. As a demonstration of this approach, we use the Gulf of Mexico (America) region, which provides critical services in the food and energy sectors amidst dwindling, quality water resources.